2010
DOI: 10.1364/oe.18.012283
|View full text |Cite
|
Sign up to set email alerts
|

Digital phase conjugation of second harmonic radiation emitted by nanoparticles in turbid media

Abstract: Abstract:We demonstrate focusing coherent light on a nanoparticle through turbid media based on digital optical phase conjugation of second harmonic generation (SHG) field from the nanoparticle. A SHG active nanoparticle inside a turbid medium was excited at the fundamental frequency and emitted SHG field as a point source. The SHG emission was scattered by the turbid medium, and the scattered field was recorded by offaxis digital holography. A phase-conjugated beam was then generated by using a phase-only spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
114
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(118 citation statements)
references
References 33 publications
1
114
0
Order By: Relevance
“…Hsieh et al established an important generalization of this principle 79 . They used digital phase conjugation instead of wavefront shaping to make the initial focus, and positioned a nanoparticle with a nonlinear response behind a scattering medium.…”
Section: The Medium As the Lensmentioning
confidence: 99%
“…Hsieh et al established an important generalization of this principle 79 . They used digital phase conjugation instead of wavefront shaping to make the initial focus, and positioned a nanoparticle with a nonlinear response behind a scattering medium.…”
Section: The Medium As the Lensmentioning
confidence: 99%
“…The PCM conjugates the phase on the mirror surface, and causes the reflected light to rewind through the path that the input light has travelled. This "time-reversal" property of PCMs has been tried in various optical applications such as aberration canceling [2,3], pulse compression [4,5], laser resonators [6,7], holography [8], and the suppression of multiple light scattering in biological tissues [9][10][11][12][13][14]. More direct demonstrations have also been performed using acoustic waves [15] and microwaves [16], where conventional electronics can directly measure and generate the phase profile in real time.…”
mentioning
confidence: 99%
“…Cui at al. and Hsieh et al have demonstrated focusing and imaging through scattering layers by digital phase conjugation [26,27]. Wavefront shaping TA M 20 40 60 80 100 120 140 160 20 40 60 80 100 120 140 160 20 40 60 80 100 120 140 160 20 40 60 80 100 120 140 160 emission emission detected detected…”
Section: Spatial Control Of Scattered Lightmentioning
confidence: 99%
“…2.26 in the time domain. The time-dependent transmission coefficient t ab (t) is the impulse response in direction b to a delta-pulse incident from angle a, 27) where F denotes the Fourier transform. The electric field E b (t) due to an arbitrary 2.4.…”
Section: Scattering Matrix Transmission Matrix and Transmission Coefmentioning
confidence: 99%
See 1 more Smart Citation